Digital Technology Adaptations in Emergency Response - Abdul Ghani, Kamarul Al Haqq Bin (International Journal of Human and Health Sciences (IJHHS), 2019)
Abstract not available International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 21